Internet Censorship? Here Comes Iran! - Ladhani, Noorin (Social Policy)
The article discusses the use of Internet censorship in Iran as its approach to block out outside information. It states that the strategy of the country became a headline on the technology sites and in mainstream media. It notes that the government blocked access to site that provides encryption using hypertext transfer protocol secure (HTTPS) including email services to prevent Iranians from conducting protests against house arrest of politicians Mir-Hossein Mousavi and Mehdi Karroubi.